Simple screening tools predict death and cardiovascular events in patients with rheumatic disease. (4th March 2018) - Breunig, M; Kleinert, S; Lehmann, S; Kneitz, C; Feuchtenberger, M; Tony, H-P; Angermann, CE; Ertl, G; Störk, S
Abstract : Objectives : Patients with rheumatic disease (RD) have an increased mortality risk compared with the general population, mainly due to cardiovascular disease (CVD). We aimed to identify patients at high risk of CVD and mortality by comparing three screening tools suitable for clinical practice. Method : In this prospective, single-centre study, consecutive patients with rheumatoid arthritis (RA), systemic autoimmune disease (SAI), or spondyloarthritides (SpA) including psoriatic arthritis underwent a comprehensive cardiovascular risk assessment. Patients were predefined as being at high risk for cardiovascular events or death if any of the following were present: European Systematic COronary Risk Evaluation (SCORE) ≥ 3%, N-terminal pro-brain natriuretic peptide (NT-proBNP) ≥ 200 pg/mL, or any pathological electrocardiogram pattern. Results : The patient population (n = 764) comprised 352 patients with RA, 260 with SAI, and 152 with SpA. After a median follow-up of 5.2 years, 6.0% of RD patients had died (7.0%, 7.2%, and 1.4% of patients in the RA, SAI, and SpA subgroups), and 5.0% had experienced a cardiovascular event (5.0%, 6.4%, and 2.8%, respectively). For all RD patients and the RA and SAI subgroups, NT-proBNP ≥ 200 pg/mL and SCORE ≥ 3% identified patients with a 3.5–5-fold increased risk of all-cause death and cardiovascular events. Electrocardiogram pathology was associated with increased mortality risk, but not with cardiovascular events. Conclusion : NT-proBNP ≥ 200 pg/mL or SCORE ≥ 3% identifies RA and SAI patients with increased risk of cardiovascular events and death. Both tools are suitable as easy screening tools in daily practice to identify patients at risk for further diagnostics and closer long-term follow-up.